Perception of socioeconomic status: A meta-analysis of manipulations - TAN, Jacinth Jia Xin (Institutional Knowledge at Singapore Management University, 2025)
The causal effects of one’s socioeconomic status (SES) on outcomes are typically examined by experimentally manipulating SES self-perceptions based on one of three SES dimensions—absolute resource, relative resource, and general social position. We investigated the efficacy of these manipulations by systematically meta-analyzing their effects on SES self-perceptions. Based on 107 eligible samples (N = 26,203), manipulations of SES self-perceptions across the three SES dimensions were effective overall (g = 0.56–0.95). Explicit priming of absolute resource and relative resource manipulations comparing high versus low SES were consistently effective—although bias-corrected effects were attenuated—suggesting the importance of salient SES information and social comparisons. Moderation tests revealed stronger manipulation effects on SES self-perceptions among samples at earlier life stages (university and younger samples) and with stronger interdependent orientation (lower independence and higher female composition). We discuss implications on understanding the determinants of SES self-perception and designing experimental studies on SES effects.